What would the great economists do? : how twelve brilliant minds would solve today's biggest problems - Yueh, Linda Y. (Linda Yi-Chuang) (Picador, 2018)
"A timely exploration of the life and work of world-changing thinkers--from Adam Smith to John Maynard Keynes--and how their ideas would solve the great economic problems we face today." -- Amazon.com.